Aspects of the ecology and biology of the Lowveld largescale yellowfish (Labeobarbus marequensis, Smith, 1843) in the Luvuvhu River, Limpopo River System, South Africa - Fouche, P.S.O. (My University, 2009)
Aspects of the ecology and biology of the Lowveld largescale yellowfish (Labeobarbus marequensis) were studied in the Luvuvhu River over a period of three years. In this study the origin of the species, its phylogenetic relation to the other South African yellowfish species, its distribution and gross morphology are discussed and the lack of knowledge regarding aspects of the species is pointed out. The study area is identified and its geology, hydrology, climate and water quality as well as the historic distribution of the species is discussed. Adapted “truss” techniques were applied to measure and calculate the morphometric features related to feeding and habitat preference of the species. From this data the habitat preferences and requirements were inferred after which it was compared to data obtained during field surveys. The study of the breeding biology and ecology of the species included investigations of gonad and egg structure and development as well as seasonal surveys of selected breeding sites. The diet of the species was established through stomach content analyses and related to the digestive tract morphology. Data obtained from the Xikundu fishway was used to establish the migratory behaviour. Results show that nine distinct stanzas or growth phases, each with its own morphometric characteristics, were identified. The body form, and some morphological aspects, of the species make it suitable to cope with flowing water. Ontogenetic changes in body form and the identified morphological aspects were observed and related to the habitat preferences of the stanzas. A distinct ontogenetic shift in preferred habitat was illustrated. The species was shown to be fractional spawner with two spawning events per annum. A major extended spawning event occurred during spring or early summer and coincided with a temperature increase and in particular with an increase in flow. Breeding occurred at sites with fast flowing water over cobble or boulder beds and it was observed that the presence of nursery areas related to breeding biotopes was extremely important. Although the diet of the species was dominated by plant and algal matter, juvenile stanzas ingested large amounts of animal material. It was found that the spatial movements of the species could be characterised as migrations and that breeding and dispersal migrations occurred.
Thesis (Ph. D. (Zoology)) -- University of Limpopo, 2009.
Keywords: Yellow fish; Ecology; Fishes -- Habitat; Fishes -- Ecology; Barbus (Fish); Aquatic habitats